Stability of Pexiderized Quadratic Functional Equation in Random 2-Normed Spaces - Mohammed A. Alghamdi (Journal of Function Spaces)
The aim of this paper is to investigate the stability of Hyers-Ulam-Rassias type theorems by considering the pexiderized quadratic functional equation in the setting of random 2-normed spaces (RTNS), while the concept of random 2-normed space has been recently studied by Goleţ (2005).